2016
DOI: 10.3402/qhw.v11.32914
|View full text |Cite
|
Sign up to set email alerts
|

Exploring beliefs around physical activity among older adults in rural Canada

Abstract: ObjectiveAs physical activity can improve health and reduce the risk of chronic disease, it is important to understand the contributing factors to physical activity engagement among older adults, particularly those living in rural communities to assist in remaining active and healthy as long as possible. The purpose of this study was to gain a deeper understanding of the socio-ecological factors that influence or contribute to physical activity among rural-dwelling older adults in rural Saskatchewan, Canada.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 21 publications
7
35
0
Order By: Relevance
“…Our findings indicate that participants valued supporting each other, empowering other residents and contributing to a more meaningful day. Parallels with our findings can be drawn from a study by Schmidt et al [36], which showed how older persons identified social activities as crucial facilitators to eventually mobilizing the strength to perform physical activities. Lorenz et al [16] also found similar indications to ours, where interventions need to be experienced as meaningful to be viewed positively.…”
Section: Towards a Nursing Home Environment That Also Takes Social Nesupporting
confidence: 88%
“…Our findings indicate that participants valued supporting each other, empowering other residents and contributing to a more meaningful day. Parallels with our findings can be drawn from a study by Schmidt et al [36], which showed how older persons identified social activities as crucial facilitators to eventually mobilizing the strength to perform physical activities. Lorenz et al [16] also found similar indications to ours, where interventions need to be experienced as meaningful to be viewed positively.…”
Section: Towards a Nursing Home Environment That Also Takes Social Nesupporting
confidence: 88%
“…The app introduced the delineation between immediate goals and long-term goals, which allowed participants to acknowledge the value of doing simple tasks, doing short bursts of exercise routines of various intensities to help them feel like accomplishing a lot. The app helped applaud participants achievements of small steps of exercise routines which were bigger successes from a feel-good perspective, which was similar to the result from the study about beliefs around PA among older adults in rural Canada (Schmidt et al, 2016). Group 2 participants were motivated by factors such as accomplishing challenges with ease, hitting pedometer targets, doing outdoor or fitness activities.…”
Section: Accomplishing a Goalsupporting
confidence: 55%
“…Our findings indicate that participants valued supporting each other, empowering other residents and contributing to a more meaningful day. Parallels with our findings can be drawn from a study by Schmidt et al [35], which showed how older persons identified social activities as crucial facilitators to eventually mobilizing the strength to perform physical activities. Lorenz et al [16] also found similar indications to ours, where interventions need to be experienced as meaningful to be viewed positively.…”
Section: Towards a Nursing Home Environment That Also Takes Social Nesupporting
confidence: 88%